When Global Brand Reputation Isn't Enough: The Role Of Product Features And Brand Image In Shaping Hp Laptop Purchase Interest - Aldena Farhana Rahman; H. Akhmad Saufi; Yeldy Dwi Genadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Although HP is one of the world's leading laptop brands with a strong global reputation, a preliminary survey indicated that it is not yet the primary choice among university students due to their evaluation of product features and perceptions of brand image. This condition highlights the need to examine the factors that influence students' purchase intention toward HP laptops. This study aims to analyze the effects of product features and brand image on the purchase intention of HP laptops among students of the Faculty of Economics and Business, University of Mataram. This research employed a quantitative approach with an associative research design. A total of 100 students were selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The results revealed that product features had a positive and significant effect on purchase intention (B = 0.403; p < 0.001), while brand image also had a positive and significant effect on purchase intention (B = 0.366; p < 0.001). Simultaneously, both variables explained 63.9% of the variance in students' purchase intention (R2 = 0.639). These findings provide empirical evidence that functional evaluation through product features and perceptual evaluation through brand image play important roles in shaping students' purchase intention toward HP laptops. The findings also offer practical insights for companies in developing product innovation and strengthening brand image strategies to better meet the needs of young consumers.